Mitochondrial DNA Fitness Depends on Nuclear Genetic Background in Drosophila. Issue 4 (1st April 2019) - Mossman, Jim A; Ge, Jennifer Y; Navarro, Freddy; Rand, David M
Abstract: Mitochondrial DNA (mtDNA) has been one of the most extensively studied molecules in ecological, evolutionary and clinical genetics. In its early application in evolutionary genetics, mtDNA was assumed to be a selectively neutral marker conferring negligible fitness consequences for its host. However, this dogma has been overturned in recent years due to now extensive evidence for non-neutral evolutionary dynamics. Since mtDNA proteins physically interact with nuclear proteins to provide the mitochondrial machinery for aerobic ATP production, among other cell functions, co-variation of the respective genes is predicted to affect organismal fitness. To test this hypothesis we used an mtDNA-nuclear DNA introgression model in Drosophila melanogaster to test the fitness of genotypes in perturbation-reperturbation population cages and in a non-competitive assay for female fecundity. Genotypes consisted of both conspecific and heterospecific mtDNA-nDNA constructs, with either D. melanogaster or D. simulans mtDNAs on two alternative D. melanogaster nuclear backgrounds, to investigate mitonuclear genetic interactions (G x G effects). We found considerable variation between nuclear genetic backgrounds on the selection of mtDNA haplotypes. In addition, there was variation in the selection on mtDNAs pre- and post- reperturbation, demonstrating overall poor repeatability of selection. There was a strong influence of nuclear background on non-competitive fecundity across all the mtDNA species types. In only one of the four cage types did we see a significant fecundity effect between genotypes that could help explain the respective change in genotype frequency over generational time. We discuss these results in the context of G x G interactions and the possible influence of stochastic environments on mtDNA-nDNA selection.